2021
DOI: 10.1038/s41467-021-22928-0
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of interferons in gastrointestinal injury repair

Abstract: The etiology of ulcerative colitis is poorly understood and is likely to involve perturbation of the complex interactions between the mucosal immune system and the commensal bacteria of the gut, with cytokines acting as important cross-regulators. Here we use IFN receptor-deficient mice in a dextran sulfate sodium (DSS) model of acute intestinal injury to study the contributions of type I and III interferons (IFN) to the initiation, progression and resolution of acute colitis. We find that mice lacking both ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 105 publications
0
30
0
Order By: Relevance
“…Also, it has been recently demonstrated that type I and type III IFNs dramatically increase expression of ACE2 and TMPRSS2 to boost viral entry in alveolar epithelial cells [ 83 ], unveiling another possible detrimental effect of these immune mediators in the lower airways of COVID-19 patients. It is, though, important to mention that studies focused on the activity of type III IFNs in the gut revealed a protective role for this group of IFNs on intestinal epithelial cells [ 84 , 85 ], as well as their capacity to reduce tissue damage by dampening neutrophils’ functions [ 86 • ]. It is possible that either the nature of the agent that drives the inflammatory process, or the duration -e.g.…”
Section: Protective and Detrimental Roles Of Ifns In Covid-19 Patientsmentioning
confidence: 99%
“…Also, it has been recently demonstrated that type I and type III IFNs dramatically increase expression of ACE2 and TMPRSS2 to boost viral entry in alveolar epithelial cells [ 83 ], unveiling another possible detrimental effect of these immune mediators in the lower airways of COVID-19 patients. It is, though, important to mention that studies focused on the activity of type III IFNs in the gut revealed a protective role for this group of IFNs on intestinal epithelial cells [ 84 , 85 ], as well as their capacity to reduce tissue damage by dampening neutrophils’ functions [ 86 • ]. It is possible that either the nature of the agent that drives the inflammatory process, or the duration -e.g.…”
Section: Protective and Detrimental Roles Of Ifns In Covid-19 Patientsmentioning
confidence: 99%
“…A gene-gene network was also constructed using FLAME to uncover clusters of SAS genes with common molecular functions (Figure S1C). Analysis of putative protein-protein interactions (physical and functional associations) through the STRING option of FLAME uncovered a cluster of interacting components of T cellassociated immunity and a cluster of interferon beta (IFNβ) response proteins implicated in epithelial regeneration upon DSS-induced tissue damage [58] (Figure 3C). To interpret SAS transcripts as biological functions and pathways, we combined KEGG and REACTOME pathway enrichment analysis using FLAME.…”
Section: Resultsmentioning
confidence: 99%
“…When IFNLR was knocked out alone or in IFNLR/IFNAR double knockouts, DSS colitis susceptibility increased compared with controls ( 55 , 56 ). In double receptor knockouts, slowed recovery from DSS colitis was associated with impaired IEC proliferation and loss of goblet cells with mucin granules ( 55 ). Increased infiltration of neutrophils and CD169+ macrophages were also observed in double receptor knockouts, but interestingly, larger increases occurred in mice deficient in only the IFNLR receptor.…”
Section: Evidence For a Protective Role Of Ifn-λ In Ibdmentioning
confidence: 95%
“…Additional studies in IFNLR knockout mice have corroborated findings that IFNLR promotes mucosal healing in the colon. When IFNLR was knocked out alone or in IFNLR/IFNAR double knockouts, DSS colitis susceptibility increased compared with controls (55,56). In double receptor knockouts, slowed recovery from DSS colitis was associated with impaired IEC proliferation and loss of goblet cells with mucin granules (55).…”
Section: Evidence For a Protective Role Of Ifn-l In Ibdmentioning
confidence: 99%
See 1 more Smart Citation